Development of an Integrated Microfluidic and TEER Measurement System for Static and Dynamic Blood–Brain Barrier Models - Rouhani, Tariq Ihsan (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.